2016
DOI: 10.3389/fphys.2016.00271
|View full text |Cite
|
Sign up to set email alerts
|

Neuroethology of Olfactory-Guided Behavior and Its Potential Application in the Control of Harmful Insects

Abstract: Harmful insects include pests of crops and storage goods, and vectors of human and animal diseases. Throughout their history, humans have been fighting them using diverse methods. The fairly recent development of synthetic chemical insecticides promised efficient crop and health protection at a relatively low cost. However, the negative effects of those insecticides on human health and the environment, as well as the development of insect resistance, have been fueling the search for alternative control tools. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 320 publications
(467 reference statements)
0
34
0
Order By: Relevance
“…Many sensory stimuli have innate valences, acquired through evolution: some stimuli are innately attractive and others are innately repulsive (Q. Li & Liberles, 2015;Reisenman et al, 2016). However, to behave adaptively in an ever-changing environment, animals are also able to learn new valences for stimuli (Q.…”
Section: Introductionmentioning
confidence: 99%
“…Many sensory stimuli have innate valences, acquired through evolution: some stimuli are innately attractive and others are innately repulsive (Q. Li & Liberles, 2015;Reisenman et al, 2016). However, to behave adaptively in an ever-changing environment, animals are also able to learn new valences for stimuli (Q.…”
Section: Introductionmentioning
confidence: 99%
“…Somewhat differently, RSV can be transmitted from female adults to their progeny via eggs, while RBSDV has no transovarial transmission . In the process that insect horizontally transmits virus to plant host, it is involved in plant host orientation of insect vector, and the orientation behavior may be driven by olfaction …”
Section: Introductionmentioning
confidence: 99%
“…4,5 In the process that insect horizontally transmits virus to plant host, it is involved in plant host orientation of insect vector, [6][7][8] and the orientation behavior may be driven by olfaction. 9,10 Like most animals, insects rely on their olfactory systems for finding food, courtship, and avoiding noxious chemicals and predators. 10 The odorant signals are mainly detected by the olfactory sensory neurons (OSNs) on the insect antennae, 11,12 which project their chemoreceptive dendrites into morphologically different types of cuticular hair structures (named the olfactory sensilla).…”
Section: Introductionmentioning
confidence: 99%
“…It is often reported that when exposed to a group of hosts (of the same species), mosquitoes seeking hosts express a preference for one individual over others (Knols et al, 1995;Qiu et al, 2006;Takken & Knols, 2018). This preference is probably caused by the natural variation in odorants between individuals, which affects insects even at very low concentrations, and demonstrates the high sensitivity of odorant receptors to semiochemicals (Reisenman et al, 2016;Zwiebel & Takken ,2004). However, the differences between species in the preference of mosquitoes by hosts are generally very robust because they are based on real differences in the composition of the odor (Majeed et al, 2016).…”
Section: Discussionmentioning
confidence: 99%